Cannabis Use and Cannabis Use Disorders in South Africa: A Narrative Review - Bako, Rutendo Robyn Alana (Journal of drug issues, 2024)
Cannabis significantly contributes to the substance use and abuse statistics in South Africa (SA), rendering it a dangerous drug into which research on the contextual motivations and long and short term effects must be conducted. The aim of this review was to determine the availability of cannabis use and CUD research in SA, identify the central issues and themes explored over the past 2 years (2020–2022), and outline literary inconsistencies and shortcomings in cannabis use and CUD-related research in SA. The 16 articles used in this study were sourced from five databases. Reflexive Thematic Analysis (RTA) was then used to analyse the findings of the study. The study revealed, literature has a thematic focus on one or more of the following: cannabis use and psychophysiological health, determinants of cannabis use and CUD, polysubstance use, legalisation of cannabis in SA, and the effects of cannabis use and CUD.